Challenging public perceptions of childcare teachers through Cixous's écriture feminine. Issue 2 (17th February 2018) - Chang-Kredl, Sandra
ABSTRACT: Cultural stories provide us with a repertoire of narratives through which we interpret and construct our understandings of the world, including our gendered understandings of the early childhood teacher. Through her notion of écriture feminine, Cixous [1976. "The Laugh of the Medusa." Trans K. Cohen and P. Cohen. Signs: Journal of Women in Culture and Society 1 (4): 875–893] wrote of countering systems of cultural texts that inscribe women as 'other'. In this paper, I conduct a critical analysis of Disney's Maleficent (2014), a recent and often deemed feminist adaptation of the Sleeping Beauty tale, to inform our understanding of the challenges faced in rewriting public perceptions of the childcare teacher in Canada today. The early childhood teacher is often constrained within gendered expectations and attempts to revise the ways society values their professional status have yet to be achieved. The analysis suggests that Maleficent offers positive directions for change, however persistent constraints on feminine identities may be particularly difficult to retract in women whose work involves significant caring and other-directedness.